Multitasking Application for Systematic Intervention Program And Games (MASIPAG) in Science: An Evaluation - Arnel Miraflor; Annalyn Raboy; Julie Ann Ealdama; Maureen Joy Maga (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Student participation has received a lot of attention in recent decades as a result of moves toward student-centeredness, as well as promising research that suggests a link between student engagement and academic success. The researchers wanted to see how computer-generated software/applications influenced the academic performance of senior high school students. The randomized Pretest-Posttest control group design was used in this study. This study included only 40 students in Grade 11. The cover of the lesson depicts science, and the materials used are computers and cellphones, with Appgeyser serving as the application that the lessons were integrated into. The games were sent to students studying science in grade 11-Life Science and installed on their cellphones by the researchers. Giving a Pre-Test before the lesson and a Post-Test after the lesson was one of the strategies used in this study for each class. For groups 1, the lesson was delivered in a modular format using technology such as a cell phone and a computer application. Based on the data gathered, the researchers concluded that students who used mobile games performed better during the post-test than students who used SLMs. The MASIPAG mobile game was also more effective in teaching life science when compared to modular learning. The use of mobile phone games versus the use of SLMs during pandemic education was found to be significantly different in post-test results. The researcher recommended that teachers use a variety of computer applications in their classrooms based on the findings and conclusions of the study. More strategies for engaging teaching-learning situations should be developed.